Job Ladder and Wealth Dynamics in General Equilibrium - Kaas, Leo; Lalé, Etienne; Siassi, Nawid (Econometrica, 2026)
This paper develops a macroeconomic model that combines an incomplete‐markets overlapping‐generations economy with a job ladder featuring sequential wage bargaining, endogenous search effort of employed and non‐employed workers, and differences in match quality. With these ingredients, our model provides a joint microfoundation for the three main inputs in aggregate production: capital, employment, and labor efficiency. The calibrated model offers a good fit to the empirical age profiles of search activity, job‐finding rates, wages, and savings. We use the model to analyze the impact of tax and transfer policies for labor market dynamics and aggregate economic activity via capital, employment, and labor efficiency channels. Lower unemployment benefits and a less progressive tax schedule bring about welfare losses for a newborn worker which are mainly driven by higher consumption risk and costlier search effort; both policies have differential effects along the age, income, and wealth dimensions.